A cross-cultural analysis on the Interpersonal meaning of attitude resources in Chinese and English online consumer reviews - Wang, Weichao; Zhang, Xiaofen (Frontiers in Psychology, 2022)
Online consumer reviews benefit not only buyers but also sellers in the virtual market place. For consumers, they can realize their attitudes to products through the various lexical attitudinal resources indicating emotion and judgement, and for sellers they act as a form of customer feedback which can enhance the relationship between buyers and sellers. In that sense they improve the operation of the market price mechanism. The purpose of this study is to investigate the Interpersonal meanings realized through the attitude resources drawn upon by English and Chinese online consumers. Based on the Appraisal System, especially the Attitude System (Martin and White, 2005) in Systemic Functional Linguistics (SFL), this study conducts a contrastive analysis of the attitudinal resources employed by consumers in Amazon UK and Amazon China. These features are analyzed by using the UAM Corpus Tool to annotate the relevant resources, with similarities and differences in the general distribution of attitudinal resources identified, and any potential underlying reasons explained. The results of this study suggest that different features and distribution of attitudinal resources are employed in English and Chinese online consumer reviews, and that more attitudinal units are involved in English online consumer reviews than in the Chinese versions. Consumers from the United Kingdom also seem to use more affect resources than Chinese consumers in their online reviews, while Chinese consumers employ slightly more judgement resources and more appreciation resources. Possible factors that may cause such differences are examined in terms of the differing contexts of cultures.